Bursting Behavior in the System of Coupled Oscillators with Delay and its Statistical Analysis - S. D. Glyzin; E. A. Marushkina (Моделирование и анализ информационных систем, 2015)
The statistical analysis of random quantities derived from the dynamics of interaction of a pair of neuron-type oscillators are presented. It is shown that computation of some statistical characteristics of the process allows, with enough precision, to distinguish two types of orbits, while their phase portraits, Lyapunov dimension and time plots are slightly different.